Real‐time assessment of potential peak local specific absorption rate value without phase monitoring: Trigonometric maximization method for worst‐case local specific absorption rate determination - Meliadò, Ettore Flavio (Magn Reson Med, 2020)
PURPOSE: Multi‐transmit MRI systems are typically equipped with dedicated hardware to sample the reflected/lost power in the transmit channels. After extensive calibration, the amplitude and phase of the signal at the feed of each array element can be accurately determined. However, determining the phase is more difficult and monitoring errors can lead to a hazardous peak local specific absorption rate (pSAR(10g)) underestimation. For this purpose, methods were published for online maximum potential pSAR(10g) estimation without relying on phase monitoring, but these methods produce considerable overestimation. We present a trigonometric maximization method to determine the actual worst‐case pSAR(10g) without any overestimation. THEORY AND METHOD: The proposed method takes advantage of the sinusoidal relation between the SAR(10g) in each voxel and the phases of input signals, to return the maximum achievable SAR(10g) in a few iterations. The method is applied to determine the worst‐case pSAR(10g) for three multi‐transmit array configurations at 7T: (1) body array with eight fractionated dipoles; (2) head array with eight fractionated dipoles; (3) head array with eight rectangular loops. The obtained worst‐case pSAR(10g) values are compared with the pSAR(10g) values determined with a commonly used method and with a more efficient method based on reference‐phases. RESULTS: For each voxel, the maximum achievable SAR(10g) is determined in less than 0.1 ms. Compared to the reference‐phases‐based method, the proposed method reduces the mean overestimation of the actual pSAR(10g) up to 52%, while never underestimating the true pSAR(10g). CONCLUSION: The proposed method can widely improve the performance of parallel transmission MRI systems without phase monitoring.